Integrating Sustainability into the Strategic Management of Financial Institutions in Developing Economies - Bahrul Ilmi (Al-Amwal : Jurnal Ekonomi dan Perbankan Syari'ah, 2024)
This study discusses the role of financial institution management in supporting sustainable development and strengthening the national economy. In the context of globalization and dynamic economic challenges, financial institutions have a strategic role in channeling responsible financing, managing risks effectively, and encouraging sustainability-oriented investment. This study examines how policies, product innovations, and governance implemented by financial institutions can create positive social, economic, and environmental impacts. Through a qualitative approach with literature studies and secondary data analysis, this study found that the integration of Environmental, Social, and Governance (ESG) principles in financial management can encourage inclusive and sustainable economic growth. The results of this study are expected to be a reference for policymakers and financial industry players in designing strategies that balance profitability and sustainability.